2020
DOI: 10.3390/cells9020308
|View full text |Cite
|
Sign up to set email alerts
|

uPAR Knockout Results in a Deep Glycolytic and OXPHOS Reprogramming in Melanoma and Colon Carcinoma Cell Lines

Abstract: Urokinase Plasminogen Activator (uPA) Receptor (uPAR) is a well-known GPI-anchored three-domain membrane protein with pro-tumor roles largely shown in all the malignant tumors where it is over-expressed. Here we have exploited the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 gene knock out approach to investigate its role in the oxidative metabolism in human melanoma and colon cancer as the consequences of its irreversible loss. Knocking out PLAUR, a uPAR-encoding gene, in A375p, A37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…To further validate the evidence that uPAR is critical for the Exos-mediated angiogenesis, we have exploited the CRISPR–CAS9 technology to obtain a robust irreversible uPAR gene knockout in A375 and M6 (Fig. 7 a, left panel), as recently published [ 29 ]. In parallel, to directly demonstrate the role of uPAR, we performed an experiment of expression rescue (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further validate the evidence that uPAR is critical for the Exos-mediated angiogenesis, we have exploited the CRISPR–CAS9 technology to obtain a robust irreversible uPAR gene knockout in A375 and M6 (Fig. 7 a, left panel), as recently published [ 29 ]. In parallel, to directly demonstrate the role of uPAR, we performed an experiment of expression rescue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, we have also shown that the MMP12-dependent uPAR cleavage is responsible for an angiogenesis impairment in HMVECs [ 42 ]. Here, to study the uPAR function in Exos, we exploited the CRISPR–Cas 9 technology to obtain a complete uPAR knockout, as recently published [ 29 ]. In this study, we reported that the uPAR silencing and, even more, the CRISPR-mediated knockout abrogate the pro-angiogenic potential of melanoma Exos both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, uPAR knockout by (CRISPR)/Cas9 approach has been shown to induce a glycolytic and OXPHOS reprogramming in melanoma and colon carcinoma cell lines. In particular, in uPAR KO cells, authors observe an increased number of mitochondria in two melanoma cell lines and an immature biogenesis of mitochondria in the colon carcinoma line, accompanied by a significant enhancement of the mitochondrial respiratory capacity and a decreased glycolysis, even though with an increased secretion of lactate [ 103 ].…”
Section: Upar and Cancer Hallmarksmentioning
confidence: 99%
“…Many studies, including our own, had focused on the features and the behavior of cancer cells after uPAR cleavage or downregulation, both in vitro and in vivo, using anti-uPAR oligodeoxynucleotide (ODN) (13,14) and miRNA (15), exploiting uPAR inactivation specific cleavage systems such as MMP-12 (16), or inhibiting its interaction with the complex "uPAR interactome" by a specific uncoupler peptide (17). In one of our previous studies, we decided to exploit the CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats)/ Cas9 technique to establish two melanoma and one colon carcinoma cell lines with a complete uPAR KO (18), to better understand its role in tumor progression, examining the typical cancer hallmarks. This wide-spreading technology, based on a naturally-occurring system that protects bacteria from phages infections (19), is particularly useful being uPAR commonly modulated by many extracellular factors such as hypoxia, cytokines and transcription factors such as NF-kB and TCF/ LEF (20) but also by cell-cell contact (21).…”
Section: Introductionmentioning
confidence: 99%